Hard-template synthesis of three-dimensional interconnected carbon networks: Rational design, hybridization and energy-related applications. (December 2019) - Zhu, Shan; Zhao, Naiqin; Li, Jiajun; Deng, Xiaoyang; Sha, Junwei; He, Chunnian
Graphical abstract: Highlights: Recent progresses of hard-template strategies for fabricating three-dimensional carbon networks (3DCNs) are highlighted. Composites combining 3DCNs with 0D/1D/2D nanomaterials are discussed in detail. Electrochemical performances of 3DCN-based materials in representative energy storage applications are presented. Abstract: Three-dimensional interconnected carbon networks (3DCNs) materials have the advantages of large specific surface area, high porosity, and high electronic and ionic conductivity. Especially, 3DCNs can combine with other nanomaterials to achieve the synergistic effect in numerous applications, such as energy storage, catalysis, and structural engineering. For the synthesis of 3DCNs, the hard template strategy is the most popular method due to its efficient and versatile process and controllable production. This paper summarized the recent progress in the approaches to constructing 3DCNs by using hard templates including metals, inorganic non-metals, etc. The composites based on 3DCNs with multi-dimensional reinforcements, such as 0D nanoparticles, 1D nanotubes/nanofibers, and 2D nanosheets are introduced. The applications of these 3DCNs composites towards energy storage and conversion devices are reviewed. Furthermore, the challenges on the hard-templated 3DCNs are discussed based on the current progress.